DIGITALIZATION OF LEARNING AT MAHKOTA TRICOM UNIVERSITY: INEVITABILITY OR MERE ILLUSION: Critical Perspective - Sungguh Ponten Pranata (Jurnal Mahkota Bisnis (Makbis), 2025)
This study critically examines the digitalization of learning at Mahkota Tricom Unggul University (MTU), Medan, Indonesia, focusing on whether it represents an inevitable transformation or merely an administrative illusion. Using a qualitative-critical approach, data were collected through interviews and observations involving 5 lecturers, 15 students, and 3 administrative staff members. The research aimed to analyze the extent to which digital learning has been systematically integrated into academic activities, identify the driving and inhibiting factors, evaluate the gap between institutional vision and practical implementation, and explore participants' perceptions of the reality of digital learning. The findings reveal that despite the visible presence of technology, digitalization at MTU remains fragmented and superficial. Lecturers and students face persistent issues, including unstable Wi-Fi, unreliable Zoom sessions, the absence of digital attendance systems, and limited e-learning storage (only 2 MB). These infrastructural weaknesses, combined with insufficient training and unclear institutional direction, have reduced digital learning to a symbolic performance rather than a pedagogical transformation. Participants expressed disappointment, describing digital learning as an additional workload without meaningful engagement. The study concludes that MTU's digitalization stands between aspiration and authenticity. The university has entered the digital vocabulary but not yet the digital culture. True transformation requires alignment between the Foundation, rectorate, lecturers, and students—ensuring that technology catalyzes academic creativity, not a cosmetic symbol of progress.